Effect of feeding pattern on the stage of primary dentition eruption in relation to growth parameters - Dhay HM Hassan; Shahbaa M Al-joranii; Baydaa A Yas; Samaneh Razeghi (College of Dentistry/ University of Baghdad, 2023)
Background: Feeding is a complicated process that involves the coordination of cardiovascular, respiratory, gastrointestinal (GI), and oropharyngeal mechanisms, with support from the musculoskeletal and craniofacial systems. The practice of feeding could be correlated with eruption stage and nutritional status in infants. Aim of the study: This study aimed to assess the relation of feeding patterns to a selected oral variable (stage of the eruption of primary teeth) and growth parameters among clinically healthy infants. Subjects and Methods: A cross-sectional comparative study on a sample of (300) infants aged between 6 and 18 months was performed in Karbala City, Iraq. The feeding pattern was investigated using an information sheet answered by parents. The stage of dental emergence was evaluated through intraoral examination. Growth parameters (height, weight, head circumference) were analyzed. Results: Bottle-fed infants had higher total tooth eruption incidence and nutritional status than the other feeding groups, but the difference was not statistically significant. Conclusion: Bottle-fed infants had the highest mean of erupted primary teeth and nutritional status.